2012
DOI: 10.1051/mmnp/20127207
|View full text |Cite
|
Sign up to set email alerts
|

Nonexistence of Coherent Structures in Two-dimensional Inviscid Channel Flow

Abstract: Abstract. Two-dimensional inviscid channel flow of an incompressible fluid is considered. It is shown that if the flow is steady and features no horizontal stagnation, then the flow must necessarily be a parallel shear flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a previous paper [12] (see also [13]), we considered the case of a two-dimensional strip with bounded section and the case of bounded flows in a half-plane, assuming in both cases that the flows v are tangential on the boundary and that inf |v| > 0: all streamlines are then proved to be lines which are parallel to the boundary of the domain (in other words the flow is a parallel flow). Earlier results by Kalisch [15] were concerned with flows in two-dimensional strips under the additional assumption v • e = 0, where e is the main direction of the strip. Lastly, in [14], we considered the case of the whole plane R 2 and we showed that any C 2 (R 2 ) bounded flow v is still a parallel flow under the condition inf R 2 |v| > 0.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In a previous paper [12] (see also [13]), we considered the case of a two-dimensional strip with bounded section and the case of bounded flows in a half-plane, assuming in both cases that the flows v are tangential on the boundary and that inf |v| > 0: all streamlines are then proved to be lines which are parallel to the boundary of the domain (in other words the flow is a parallel flow). Earlier results by Kalisch [15] were concerned with flows in two-dimensional strips under the additional assumption v • e = 0, where e is the main direction of the strip. Lastly, in [14], we considered the case of the whole plane R 2 and we showed that any C 2 (R 2 ) bounded flow v is still a parallel flow under the condition inf R 2 |v| > 0.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%